2013
DOI: 10.7498/aps.62.130308
|View full text |Cite
|
Sign up to set email alerts
|

Self-trapping and periodic modulation of Fermi gases in optical lattices

Abstract: The change of phase space and periodic modulation of Fermi gas from the BCS to unitarity is investigated in one-dimensional optical lattice. Through controlling the scattering length and coupling constant in unitarity, we find the critical values (from the Josephson oscillation to the oscillating-phase-type self-trapping and from the latter to the self-trapping), at the same time, we also find the relationship between the critical coupling constants and the scattering length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It is shown that there are four different phases, which are Josephson oscillation (JO), oscillatingphase-type self-trapping (OPTST), running-phase-type selftrapping (RPTST), and self-trapping (ST). [27][28][29][30][31][32][33] It is noted that the number density of the Fermi gas and the scattering length play a crucial role on the the trapping and tunneling of the Fermi gases. Some phenomena are observed and the explanations are given.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that there are four different phases, which are Josephson oscillation (JO), oscillatingphase-type self-trapping (OPTST), running-phase-type selftrapping (RPTST), and self-trapping (ST). [27][28][29][30][31][32][33] It is noted that the number density of the Fermi gas and the scattering length play a crucial role on the the trapping and tunneling of the Fermi gases. Some phenomena are observed and the explanations are given.…”
Section: Introductionmentioning
confidence: 99%